Methods to prevent baby pig anemia - Koch, B.A.; Stuart, J.G.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three trials were conducted involving 231 head of pigs to determine the efficiency of various methods of providing supplemental iron to baby pigs. All treatment groups were effective in maintaining normal hematocrit values with no symptoms of baby pig anemia. Weight gains were similar in all trials.
Swine Industry Day 1970 is known as Swine Day, 1970
Keywords: Swine; Anemia